2008
DOI: 10.1080/11250000701692729
|View full text |Cite
|
Sign up to set email alerts
|

Spatial niche of the Italian cave salamander,Speleomantes italicus(Dunn, 1923) (Plethodontidae, Amphibia), in a subterranean system of Central Italy

Abstract: A study was carried out on the population structure and spatial niche of Speleomantes italicus (Dunn, 1923) in a subterranean system of 10 caves in Umbria (Italy). The studied populations revealed a peak of activity from April to July. The relative abundance of salamanders varied throughout the year and the observed frequencies of individuals differed significantly from expected, confirming a seasonal pattern of activity. Both external and internal temperatures positively influenced the abundance of salamande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 8 publications
(18 reference statements)
2
10
0
Order By: Relevance
“…Our models show that H. strinatii does not occur randomly in caves. In accordance with previous studies on microhabitat use by cave salamanders (Briggler and Prather, 2006;Lanza et al, 2007;Vignoli, Caldera and Bologna, 2008), the distribution pattern suggests that these salamanders select caves with specific features, and both abiotic and biotic parameters seem to be extremely important factors determining habitat selection. Our models also provide methodological suggestions that can be useful for other studies focusing on cave salamanders.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our models show that H. strinatii does not occur randomly in caves. In accordance with previous studies on microhabitat use by cave salamanders (Briggler and Prather, 2006;Lanza et al, 2007;Vignoli, Caldera and Bologna, 2008), the distribution pattern suggests that these salamanders select caves with specific features, and both abiotic and biotic parameters seem to be extremely important factors determining habitat selection. Our models also provide methodological suggestions that can be useful for other studies focusing on cave salamanders.…”
Section: Discussionsupporting
confidence: 87%
“…In accordance with previous studies (Briggler and Prather, 2006;Lanza et al, 2006Lanza et al, , 2007Vignoli et al, 2008), we found a significant relationship between salamanders and the most humid and cold caves, which often have wet walls. Cave salamanders have narrow physiological limits (Brattstrom, 1963;Spotila, 1972;Lanza et al, 2006), and their presence in caves is probably determined by the species requirements to escape the hot, dry conditions, especially during summer (Cimmaruta et al, 1999;Briggler and Prather, 2006).…”
Section: Environmental Features and Distribution Of Cave Salamanderssupporting
confidence: 95%
“…Cave salamanders have direct development. They are not obligate cave-dwellers but, when external conditions would be too harsh (e.g., dry, hot, and particularly during warm seasons) for lungless terrestrial salamanders, they retreat to underground environments where they find a more suitable microclimate (Cimmaruta et al 1999;Camp and Jensen 2007;Vignoli et al 2008;Ficetola et al 2012). When in the cave environment, they are easily detectable (Ficetola et al 2012) and show extremely limited displacements; for instance, in H. strinatii, each individual usually occupies areas B8m 2 (Salvidio et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Most recent studies about the ecological niches of subterranean organisms focus on specific model taxa, such as cave salamanders (e.g., Vignoli et al. ; Lunghi et al. ), carabid and cholevid beetles (Crouau‐Roy et al.…”
mentioning
confidence: 99%
“…Most recent studies about the ecological niches of subterranean organisms focus on specific model taxa, such as cave salamanders (e.g., Vignoli et al 2008;Lunghi et al 2015), carabid and cholevid beetles (Crouau-Roy et al 1992;Mammola et al 2015a), and hymenopterans (during their hypogean ecophase; Novak et al 2010a). Concerning spiders, a few authors have described the niches of medium-to large-sized species occurring in the twilight zone [troglophiles sensu Sket (2008)] such as Metellina merianae (SCOPOLI 1763) (Novak et al 2010b), Meta menardi (LATREILLE 1804) (Bourne 1976;Novak et al 2010b;Mammola & Isaia 2014;Chiavazzo et al 2015;Manenti et al 2015), and Meta bourneti SIMON 1922 (Mammola & Isaia 2014).…”
mentioning
confidence: 99%